PENGARUH GAYA KEPEMIMPINAN DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA KARYAWAN FKIP UNS - Hanna Laili Rashuan; Hery Sawiji; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2020)
The research usess quantitativei descriptivei methods. The respondentsi of this non-educativei employeesi of Teacher Training and Education Faculty in Sebelas Maret University to help studenti for administration services as 111 employees. Thei technique in research there are use saturated sampling. Data collectioni techniques there use questionnairesi and documentation. Questionnairesi are usedi to collecti data on leadership istyle and interpersonali communication, while documentation is used to collect data base employee. The data analysis technique used is multiple regression analysis. The results of this study are: (1) There is a significant effect of leadership style on the Teacher Training and Education Faculty in Sebelas Maret University as indicated by the t count value of the leadhershipi style variable is 3,184 > t table is 1,982 and sig. 0,000 < 0,05. (2) There is a significant influence There is a significant influence on the interpersonal communication to the employee performance Teacher Training and Education Faculty in Sebelas Maret University as indicated by the t count value of the interpersonali communication is 6,043 > t table is 1,982 and the value of sig. 0,000 < 0,05. (3) There is a significant influence on the leadership style and interpersonal communication together on the employee performance Teacher Training and Education Faculty in Sebelas Maret University as indicated by F count value greater than F table, which is 33,661 > 3,08.